SEA: Towards Slicing Elasticity as a Service - Rocha, André Luiz B.; Maciel Jr., Paulo Ditarso; Verdi, Fabio Luciano (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2024: Anais do XLII Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos, 2024)
In this paper, we address the challenge of supporting slice resource elasticity within an orchestrated closed control loop (CCL) to ensure Service Level Agreements (SLAs) based on pre-defined Key Performance Indicators (KPIs). We introduce the service model Slicing Elasticity as a Service (SlEaaS) and define the Slice Elasticity Architecture (SEA) to fulfill the gap of orchestration in the context of slices. The SEA offers a comprehensive CCL for orchestrating slice resources and enables a range of elasticity operations on different resource types. These operations are facilitated across diverse administrative and technological domains. This architecture allows tenants or slice providers to autonomously monitor slice resources and perform elasticity operations when KPI violations occur. The obtained results demonstrate the functionality of SEA through various scenarios of elasticity operations on network resources. We cover essential aspects such as component instantiation, slice resource monitoring, KPI definitions, and the execution of elasticity operations to ensure compliance with the tenant’s SLA.